Determinants of Households’ Adaptation Practices against Climate Change Impact on Off Farm Activities in Nepal - Dhungana, Ananta Raj; Khand, Purna Bahadur (Janapriya Journal of Interdisciplinary Studies, 2019)
Study on adaptation practices against climate change impact in agriculture sector have been explored extensively globally but adaptation practices against climate change impact on off farm activities are not studied in detail. This study aims to analyze the determinants of households’ adaptation practices against climate change impact on off farm activities in Nepal. It utilizes the data generated from nationally representative samples of National Climate Change Impact Survey, 2016 conducted by Central Bureau of Statistics. Total sample size of this survey was 5060 households. But for this paper, total of 4114 samples were considered. Binary logistic regression analysis was carried out to analyze households’ adaptation practices against climate change impact on off-farm activities in Nepal. Most of the respondents are male of age 40-54 years, from non-Brahmin/Chhetri caste/ethnicity, illiterate, with lowest income Quintile, from tropical climate zone and without getting any services from agricultural service center. Females ageless likely to have adaptation practices towards off farm activities (started more off-farm activities; shifted to non-agricultural employment; and temporary out-migration) in compared with male. Non-Brahmin/Chhetri caste/ethnicity with reference to Brahmin/Chhetri is the determining factor for the adaptation practices (shifted to non-agricultural employment; and temporary out-migration). Status of receiving any services from agricultural service center, years of experience in agricultural sector and sub-tropical climate zone with reference to tropical zone are the common determining factors for households’ adaptation practices towards off farm activities against climate change impact in Nepal.